PENGARUH MODEL FLIPPED CLASSROOM BERBANTUAN MEDIA INTERAKTIF CANVA TERHADAP HASIL BELAJAR IPAS SISWA KELAS VI SD NEGERI GAROT ACEH BESAR - Ainul Zahra, Cindi; Tursinawati; Hasniyati (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Limited learning time with a broad scope of material and the less than optimal use of smartphones as a learning tool cause students to experience difficulties in understanding the science and natural sciences material. Learning that is still dominated by teacher explanations makes learning time less efficient and the material is not conveyed completely, thus impacting low student learning outcomes. This study aims to determine the effect of the implementation of the flipped classroom model assisted by Canva interactive media on the science learning outcomes of sixth-grade students at Garot Aceh Besar Elementary School. This study uses a quantitative approach with a quasi-experimental type through a nonequivalent control group design. The study population was all sixth-grade students, with class VI-A as the experimental class and VI-B as the control class. Data were collected through learning outcome tests in the form of pretests and posttests, then analyzed using the N-gain test, normality test, and Independent Samples t-Test. The results showed that the average learning outcomes of students in the experimental class were higher than those in the control class. The Independent Samples t-Test yielded a significance value of 0.001 < 0.05, indicating a significant effect of the flipped classroom model with the aid of Canva interactive media on the science learning outcomes of sixth-grade students at Garot State Elementary School, Aceh Besar. Thus, this learning model can be used as an alternative effective science learning strategy with the support of school facilities and infrastructure.